Pembelajaran dalam Pandangan Teori Belajar - Junaidin Junaidin (UIN Mataram, 2022)
Implementation of learning is synonymous with design and planning, not suddenly and spontaneously. The purpose of this article is to discuss four learning theories, namely: behaviorism theory, information processing theory, situated learning theory, and constructivism theory and their implications for learning design and practice. The results of this article state that, first, the theory of behaviorism recognizes that learning is a response between stimulus and response, which then requires willingness, practice, and reinforcement effects on the part of students. Second, information processing theory shows that learning is not only a change in cognitive and information content, but also the internalization of information that is reflected in attitudes and behavior. Third, situated theory says that learning is a change in behavior that will be more meaningful if applied in everyday life or the real world (internalization). Fourth, constructivism theory emphasizes the construction of learned meanings so that they can be understood properly and then be able to reconstruct new meanings when faced with the same or similar knowledge. Keywords: learning theory, behaviorism theory, information processing theory, situated learning theory, and constructivism theory. Abstrak: Pelaksanaan pembelajaran identik dengan desain dan perencanaan, tidak tiba-tiba dan spontan. Tujuan dari artikel ini adalah untuk membahas empat teori belajar, yaitu: teori behaviorisme, teori pemrosesan informasi, teori belajar situasional, dan teori konstruktivisme serta implikasinya terhadap desain dan praktik pembelajaran. Hasil dari artikel ini menyatakan bahwa, pertama, teori behaviorisme mengakui bahwa belajar adalah respon antara stimulus dan respon, yang kemudian membutuhkan kemauan, latihan, dan efek penguatan (baik positif maupun negatif) dari pihak siswa. Kedua, teori pemrosesan informasi menunjukkan bahwa belajar bukan hanya perubahan kognitif dan konten informasi, tetapi juga internalisasi informasi yang tercermin dalam sikap dan perilaku. Ketiga, teori situasional mengatakan bahwa belajar adalah perubahan perilaku akan lebih bermakna jika diaplikasikan dalam kehidupan keseharian atau dunia nyata (internalisasi). Keempat, teori konstruktivisme menekankan konstruksi makna yang dipelajari agar dapat dipahami dengan baik dan kemudian mampu merekonstruksi makna baru ketika dihadapkan pada pengetahuan yang sama atau serupa.